The Influence of Emotional Intelligence on Student Learning Outcomes at Religion-based High School in Indonesia - Eriani (Journal of Pedagogy and Education Science, 2024)
This study investigates the impact of emotional intelligence on the mathematics learning outcomes of 4th-grade students at MIS Harisma Pulo Padang, Labuhanbaru Regency, Indonesia. Employing quantitative research methodology, the descriptive analysis indicates that emotional intelligence maintains a constant value of 66.008. Furthermore, the regression coefficient for the emotional intelligence variable is calculated at 0.256, signifying that for every unit increase in emotional intelligence, there is a corresponding increase of 0.256 in learning outcomes, as expressed in the simple regression equation Y = 66.008 + 0.256X. The calculated t value for emotional intelligence stands at 0.00, supporting the acceptance of Ha, which asserts a positive correlation between emotional intelligence and mathematics learning outcomes. Moreover, the F probability value (F-calculated) of 0.004 < 0.05, along with t= 3.100 and t-table = 2.029, indicates that the condition t-count > t-table is met. Consequently, with a determination coefficient of 21.1%, Ha is affirmed while H0 is rejected, implying that the linear regression equation model, based on the research data, is statistically significant and complies with linearity criteria. In conclusion, emotional intelligence significantly influences mathematics learning outcomes.